2020
DOI: 10.1186/s12880-020-00446-7
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomography colonography versus colonoscopy for detection of colorectal cancer: a diagnostic performance study

Abstract: Background: Colonoscopy is the reference standard for the detection of colorectal cancer but it is an invasive technique and has the risk of bowel perforation and bleeding. Unlike colonoscopy, sedation is not required in computed tomography colonography and requires additional reassurance endoscopy. The objectives of the study were to compare the diagnostic performance of computed tomography colonography against colonoscopy for a diagnosis of colorectal cancer. Methods: Data regarding any polyp ≥10 mm diameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Beneficial score analyses to perform colectomies for CTC and colonoscopy were evaluated as per Eq. 4 [ 19 ]. The higher the beneficial score, the easier will be the colectomy at a low level of diagnostic confidence for the colorectal surgeons.…”
Section: Methodsmentioning
confidence: 99%
“…Beneficial score analyses to perform colectomies for CTC and colonoscopy were evaluated as per Eq. 4 [ 19 ]. The higher the beneficial score, the easier will be the colectomy at a low level of diagnostic confidence for the colorectal surgeons.…”
Section: Methodsmentioning
confidence: 99%
“…CT colonography of course does expose the patient to radiation, and other concerns include limited detection of sub centimeter polyps, and it only providing imaging rather than removal or biopsy of lesions. Extra-colonic findings are common however, recent studies have found it to be more cost effective and a reasonable alternative to colonoscopy in asymptomatic and average risk patients [32][33][34].…”
Section: Screening Methodsmentioning
confidence: 99%
“…It has demonstrated a high degree of accuracy and specificity, especially for polyps over 10 cm. For those polyps smaller than 10 cm, it shows good specificity if the polyps have other suspicious characteristics [ 59 ]. The cost of CTCs was found to be less than that of colonoscopies, which is consistent with the findings of the SIGGAR trials, which compared CTC and conventional colonoscopies in 21 national health service hospitals [ 60 ].…”
Section: Reviewmentioning
confidence: 99%